Analisis Handling Complaint Tamu Yang Menginap Di Grand Basko Hotel Padang - Wilvha Juliana; Dwi Pratiwi Wulandari (Lembaga Pengembangan Kinerja Dosen, 2024)
This research began with guest complaints regarding the follow-up carried out by staff when complaints were submitted by guests at the Grand Basko Hotel Padang. This research aimed to analyze and describe the handling of guest complaints at the Grand Basko Hotel Padang in terms of the HEAT method. Through this research, researchers has found out the analysis of handling complaints from guests staying at the Grand Basko Hotel Padang. This type of research is descriptive research with qualitative data. The informants in this study consisted of nine people divided into six hotel staff and three guests. Data collection was carried out through interviews, observation and documentation. Then, the data is processed to be reduced, presented and conclusions drawn. The data from this research were tested using source triangulation, method triangulation and time triangulation. The research results show that in handling guest complaints, Grand Basko Hotel Padang staff have applied a listening attitude, empathy, apologies, then implemented actions and follow-up.